If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -19 = 17 Reorder the terms: -19 + 4y = 17 Solving -19 + 4y = 17 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 4y = 17 + 19 Combine like terms: -19 + 19 = 0 0 + 4y = 17 + 19 4y = 17 + 19 Combine like terms: 17 + 19 = 36 4y = 36 Divide each side by '4'. y = 9 Simplifying y = 9
| 5x/4-3/4=7/4 | | 67/2a-15 | | y=100e^8x | | (18)2+(x)2=(x+14) | | 21/.75 | | 7x^2+10=9 | | 5(x-4)=-3(x+2)+33 | | 0=x^2+14-45 | | 5x-3x+12=35-4x-9 | | M^2+15+56=0 | | 1+3lnx=0 | | 5(x-4)-3(x+2)=33 | | 48+6x=84 | | 19=7x+4x+8 | | 400=60p+4p^2 | | 18x^2+9=18 | | m=11/16 | | M+7+7=23+7 | | u/3=4.8 | | 5(x-14)+2x=5x | | 24/3^2/3 | | (x+5)(75-x)= | | 5/6=x/21 | | Y(a)=x(b) | | -1(-2)(-3)(-4)= | | 5x-(14+2x)=33 | | 9x-47=7 | | 15a^2+5a-3=0 | | f(-x)=6x^2+7x-6 | | y^2-90=13*y | | 5(x+14)=3(x-11) | | c+48=3c |